THE LEVEL OF GENERAL PHYSICAL PERFORMANCE OF PUPILS ATTENDING THE FIRST GRADES AT PRIMARY SCHOOLS IN BANSKÁ BYSTRICA (Fiep Bulletin - online, 2014)
This contribution deals with the level of general physical performance of 7 years old pupils attending primary schools. Firstgrade pupils at primary schools in Banská Bystrica were tested. Tested group consisted of pupils from all primary schools. The following indicators of general physical performance were monitored: sit-and-reach, standing long jump, sit-ups in 30 s, flexed arm hang, shuttle run 4x10 meters, endurance shuttle run. Also basic somatic indicators such as body height, body weight and BMI were found out. However, we monitored an after-school physical activity as well. The results are compared to other authors dealing with the general physical performance of mentioned age group. Acknowledgment: This contribution was written with the support of grant project VE GA 1/1158/12.
Keywords: physical education; primary schools; first-grade pupils; general physical performance; somatic characteristics